Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 2 - Nonlinear Functions - 2.4 Exponential Functions - 2.4 Exercises: 9



Work Step by Step

The answer is A, because when x=0, $2-3^{-x} = 2-1 =1$ So $y=1$. And also when x=-1, $2-3^{-x} = 2- 3 =-1$ So $y = -1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.